1995
DOI: 10.1002/ddr.430360105
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of FK453: A potent non‐xanthine adenosine A1 receptor antagonist

Abstract: The renal effects of FK453, a potent and selective non-xanthine adenosine A, receptor antagonist, were examined and compared with FR113452 (less active enantiomer o i FK453), typical adenosine receptor antagonists, and diuretics. In rats FK453 possessed diuretic activity similar to 1,3-dipropyl-8-cyclopentylxanthine (DPCPX, adenosine A , receptor antagonist), hydrochlorothiazide, and furosemide, but neither FR113452 nor CP66713 (an adenosine AL receptor antagonist) possessed diuretic activity. Urinary uric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…On the other hand, FK453 and hydrochlorothiazide increased C,,, and free water reabsorption during antidiuresis, whereas furosemide increased C, , , but had little effect on free water reabsorption. These results suggest that FK453 produced potent diuretic and natriuretic effects by suppressing water and sodium transport in the proximal part of the nephron (42).…”
Section: Diuretic Activitymentioning
confidence: 73%
See 4 more Smart Citations
“…On the other hand, FK453 and hydrochlorothiazide increased C,,, and free water reabsorption during antidiuresis, whereas furosemide increased C, , , but had little effect on free water reabsorption. These results suggest that FK453 produced potent diuretic and natriuretic effects by suppressing water and sodium transport in the proximal part of the nephron (42).…”
Section: Diuretic Activitymentioning
confidence: 73%
“…We feel, therefore, that FK453 differs from hydrochlorothiazide and furosemide in its hemodynamic effects as well as its tubular site of action. Our previous study in pentobarbital anesthetized dogs demonstrated that FK453 significantly increased renal blood flow and GFR, but hydrochlorothiazide had little effect on either parameter (42).…”
Section: Renal Protective Effectmentioning
confidence: 89%
See 3 more Smart Citations